2019
DOI: 10.1080/02602938.2019.1696944
|View full text |Cite
|
Sign up to set email alerts
|

Objective outcome evaluation of a leadership course utilising the positive youth development approach in Hong Kong

Abstract: This study adopted a single-group pretest-posttest design to explore the changes in 2,876 undergraduate students in positive youth development, psychological well-being and desired graduate attributes after they took a leadership subject utilising the positive youth development approach at one university in Hong Kong. The subject aims to promote undergraduates' leadership qualities, particularly their intra-and inter-personal competencies. Participants completed the same objective outcome evaluation forms befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 60 publications
(95 reference statements)
1
21
0
Order By: Relevance
“…It would be more insightful to include objective outcome evaluation as a method for triangulation, as it would be able to demonstrate findings such as students' transformation before and after SL participation (Strage 2000). The collection of pretest and posttest data as a routine practice would be helpful (Li and Shek 2019). Additionally, qualitative evaluation could have shed more light on the subjective experiences underlying the statistics, such as why some activities were better received by service recipients.…”
Section: Discussionmentioning
confidence: 99%
“…It would be more insightful to include objective outcome evaluation as a method for triangulation, as it would be able to demonstrate findings such as students' transformation before and after SL participation (Strage 2000). The collection of pretest and posttest data as a routine practice would be helpful (Li and Shek 2019). Additionally, qualitative evaluation could have shed more light on the subjective experiences underlying the statistics, such as why some activities were better received by service recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Topics covered in the course include seven intrapersonal competences and four interpersonal competences which have been considered as being required for success in a rapidly changing society (Dede, 2010), such as self-leadership, communication skills, team-building and conflict resolution, and emotional competence. Each lecture focuses on a specific topic pertinent to an important soft skill or PYD attribute (Li & Shek, 2020). Roles of these qualities in effective leadership and university graduates' employability in the service economy are also highlighted with ample examples.…”
Section: Tomorrow's Leaders: a Leadership Course Based On The Pyd Approachmentioning
confidence: 99%
“…A rigorous evaluation was thus needed to understand the perceived effectiveness of this PYD program and to facilitate further improvement. By using the one-group pretest-posttest approach, Li and Shek (2020) reported that the students who attended the "Tomorrow's Leaders" course in three academic years (between 2015/16 and 2017/18) showed improvement in most of the 15 PYD attributes. However, evidence on the experiences and opinions of students who are the program recipients remains inadequate.…”
Section: Subjective Outcome Evaluationmentioning
confidence: 99%
“…Zhou et al [30] uncovered that PYD attributes could protect young people from depression. Although the benefits of PYD have been widely studied among adolescents, they have seldom been explored in university students [28,31].…”
Section: Introductionmentioning
confidence: 99%